The local museum in the global village : rethinking ideas, functions and practices of local history museums in rapidly changing diverse communities - Müller, Insa (Edition Museum, 2020)
In remote areas of Europe, local history museums struggle to connect with the rapidly changing and increasingly diverse communities around them. This book asks how these museums can recast themselves to strengthen the links to their communities. Combining theoretical deliberations, empirical investigations of the case of two Norwegian islands and a museum experiment, this book offers starting points for rethinking this institution, while at the same time providing suggestions for locally adapted museum practice. The book is of interest to anyone interested in the present and future of local history and small local history museums in times of major demographic transformation.